Failure or future? Exploring alternative antibacterials: a comparative analysis of antibiotics and naturally derived biopolymers - Sceglovs, Artemijs; Skadins, Ingus; Chitto, Marco; Kroica, Juta; Salma-Ancane, Kristine (Frontiers in Microbiology, 2025)
The global crisis of antimicrobial resistance (AMR) is escalating due to the misuse and overuse of antibiotics, the slow development of new therapies, and the rise of multidrug-resistant (MDR) infections. Traditional antibiotic treatments face limitations, including the development of resistance, disruption of the microbiota, adverse side effects, and environmental impact, emphasizing the urgent need for innovative alternative antibacterial strategies. This review critically examines naturally derived biopolymers with intrinsic (essential feature) antibacterial properties as a sustainable, next-generation alternative to traditional antibiotics. These biopolymers may address bacterial resistance uniquely by disrupting bacterial membranes rather than cellular functions, potentially reducing microbiota interference. Through a comparative analysis of the mechanisms and applications of antibiotics and antibacterial naturally derived biopolymers, this review highlights the potential of such biopolymers to address AMR while supporting human and environmental health.